Climatology of the main (24-h and 12-h) tides observed by meteor radars at Svalbard and Tromsø: Comparison with the models CMAM-DAS and WACCM-X. (1st October 2020) - Pancheva, D.; Mukhtarov, P.; Hall, C.; Meek, C.; Tsutsumi, M.; Pedatella, N.; Nozawa, S.; Manson, A.
Abstract: The paper presents climatology of the mean winds and diurnal and semidiurnal tides observed by meteor radars at high latitudinal stations Svalbard (78°N, 16°E) and Tromsø (70°N, 19°E) based on 18 years (2001–2018) and 16 years (2003–2018) of measurements, respectively. The main focus of the study is to clarify the features of the diurnal tide (DT) because it is poorly known particularly at high latitudes. The detailed analysis of both tidal amplitudes and phases indicated that the seasonal and altitude structure of the DT at these two not very distant stations are significantly different. Moreover, a very unusual vertical structure of the DT at Tromsø has been found where above altitudes of 88–90 km the zonal and meridional components have opposite directions of vertical propagation. This unusual vertical tidal feature has been supported by the climatology of the DT obtained by the MF radar situated at Tromsø for the period of time 1997–2019. The paper presents also the comparison of the radar observations with two models: the assimilated CMAM-DAS and the specified dynamics (SD) WACCM-X. The WACCM-X simulated DT supports to large extent the climatology of the DT at Tromsø while the assimilated CMAM-DAS reproduced the evanescent character of the tide in summer up to altitude of 88 km with almost the same amplitudes and phases as the observed ones. These results could be used as benchmarks for model simulations for understanding the forcing mechanisms of the DT at high latitudes of the considered region. Highlights: Climatology of mean winds, DT and SDT observed by meteor radars at Svalbard and Tromsø is presented. A main focus is to clarify the features of the poorly known DT at high latitudes. A very unusual vertical structure of the DT at Tromsø has been found. Comparisons of radar observations with two models: CMAM-DAS and SD-WACCMX are presented.